Violence & Conflict in Television News: A Content Analysis of The News Channels: Violence & Conflict in Television News: A Content Analysis of The News Channels - Awan, Dr. Muhammad Tariq; Ghauri, Muhammad Junaid; Alam, Riffat Alam (Journal of Peace, Development and Communication, 2022)
News media has been a source of multifarious information and has developed to a varied extent in the recent past. There now appears to be an increasing surge of propagation and dialogue on violence-related issues. Media violence has remained a viable topic of past researches because of its impact on the society and many studies focused on entertainment contents. This study is aimed at to analyze the proportion of violence in news broadcasts and to explore the role of news channels whether they cover all or focus on specific issues. A total of 2577 stories were collected from 93 news broadcasts of 9 p.m. on “top 3” news channels; Dunya News, Geo News and PTV News covering a period of one month in January 2014. Of them, 1132 news stories were identified as ‘violent,’ which were further analyzed for the extent and nature of violence and their inclusion in the news bulletin. The study concludes that selected news channels presented less proportion of violence in terms of number of stories and total stories per hour, but allocated large amount of broadcast time to small number of violent stories as compared to other issues. They reported political violence-related issues more frequently and there is large content of violence in the headlines especially on private channels.